2013
DOI: 10.1017/s0950268813000393
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence survey on measles, mumps, rubella and varicella antibodies in healthcare workers in Japan: sex, age, occupational-related differences and vaccine efficacy

Abstract: SUMMARYA seroprevalence survey on measles, mumps, rubella and varicella was conducted on healthcare workers (HCWs) at Shimane University Hospital, Japan utilizing an enzyme immunoassay. Of 1811 HCWs tested, 91·8% were seropositive to measles, 92·1% to mumps, 89·5% to rubella and 96·3% to varicella. Sex-related differences in seroprevalence were found in rubella (males vs. females: 84·7 vs. 92·2%, P < 0·001). Moreover, males aged 30–39 years were most susceptible to rubella (22·4%), which may be attributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
4
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 21 publications
7
43
4
7
Order By: Relevance
“…Because it is difficult for some hospital workers to confirm their vaccination records at the time of recruitment, it is considered to be reasonable for workers to undergo measurement of the antibody titers against measles and rubella to determine immunoprotection, despite the existence of a documented vaccination record (8). Our present survey of hospital workers in July and August 2013 showed rates of seropositivity similar to those in previous studies of Japanese healthcare workers (17,18). The percentages of subjects who remained positive for antibodies against measles and rubella in two separate tests within 5 years were 97.4% and 86.1%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Because it is difficult for some hospital workers to confirm their vaccination records at the time of recruitment, it is considered to be reasonable for workers to undergo measurement of the antibody titers against measles and rubella to determine immunoprotection, despite the existence of a documented vaccination record (8). Our present survey of hospital workers in July and August 2013 showed rates of seropositivity similar to those in previous studies of Japanese healthcare workers (17,18). The percentages of subjects who remained positive for antibodies against measles and rubella in two separate tests within 5 years were 97.4% and 86.1%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of HCW with protective rubella antibodies in Catalonian health centers included in this study (97.2%) is higher than that found in other studies, [19][20][21][22][23] probably due to the vaccination programs performed in Catalonia since 1978. A Saudi Arabian study 19 found a prevalence of antibodies of 90%.…”
Section: Discussioncontrasting
confidence: 67%
“…Considering these situations, alternative vaccination schedules for infants have been postulated, including vaccinating earlier, e.g. at 8 months of age [25,30,88,91]. Others suggest that delaying vaccination until 14 months of age [20] would enable the infant's immune system to develop, thereby producing a better immune response.…”
Section: Major Findings Of the Reviewmentioning
confidence: 99%